Writing of rights to provision of interest reward after the judgment of the tax court associated in tax disputes in customs - Hariyasin,; IBR Supancana,; Slamet Suhartono,; Fajar Sugianto, (Technium Social Sciences Journal, 2020)
The largest source of income for the Indonesian state to date is from taxes and other levies, because it’s coercive and for the purposes of the state it must be regulated by law, which is authorized for implementation by officials of the Directorate General of Taxes and officials of the Directorate General of Customs and Excise, but in its application it can there is a dispute. For this reason, dispute resolution through the Tax Court is needed which is expected to create justice and legal certainty. There are 2 (two) problems, namely 1) The executorial power of the decision of the Judge of the Tax Court Council, 2) The provision of interest compensation for excess payments after the decision of the Panel Judge at the Tax Court in the Customs sector. This research is a juridical normative, which uses a statutory approach, a conceptual approach, a case approach, a historical approach, a comparative approach and a philosophical approach. Regarding the decision of the Tax Court which has executorial power, a system of payment and return that is fast and impartial should be needed, namely a place for depositing deposits of funds managed by a third party. Regarding the legal vacuum due to the nonregulation of interest compensation for overpayments in the Customs Law, the Tax Court judges should be able to find the law.